Особливості обчислення середньоденної заробітної плати для розрахунком за листком непрацездатності - Нікітіна, Я. В. (Видавництво Львівської політехніки, 2014)
Розглянуто процес розрахунку середньоденної заробітної плати для нарахування матеріального забезпечення за тимчасової втрати працездатності та відображення в системі бухгалтерського обліку розрахунків з відшкодування працівникам втраченого заробітку. Досліджено методику розрахунку середньоденної домоги з тимчасової втрати працездатності для різних категорій найманих працівників, зокрема для добровільно застрахованих осіб. The scientific article the features of accounting of payments for insurance and reporting in accordance with applicable law are considered. The process of calculating the average wage per day to charge the material security while temporary disability and representation of workers' lost earnings compensation calculations in the business accounting is considered in the article. Reveals the method of calculating refunds for various types of social insurance are some controversial points in calculating such amounts. The features of calculating benefit for temporary disability, depending on the cause of disability: total temporary disability, caring for a sick family member, temporary disability related to pregnancy and childbirth are analyzed. Examples of calculation of the average wage per day for the employee in an insurance case and reflection the accounting in a table are considered. The methods of average benefit calculation for the period of disability for different categories of employees including the ones who work part-time and who are voluntarily insured are researched. Formulated some proposals for improving the calculation of financial security in the system of voluntary insurance.
The features of computing average daily wage for the calculation of temporary disability
Keywords: застрахована особа; добровільно застрахований; листок непрацездатності; найманий працівник; нарахування допомоги; середньоденна заробітна плата; тимчасова непрацездатність; average wage per day; calculation of payments; disability leaf; employee; insured person; temporary disability; voluntarily insured